Derivatives of Products

Example:
y = (x - 1) (x - 2) (x - 3)

The first thing to notice when finding the derivative of this function is that it is the product of several terms, as shown in color below:

y = ( x - 1) ( x - 2) ( x - 3)

The Derivative Rule for Products:

The derivative of a product is the derivative of the first term times the second (and third, etc.) term(s), plus the first (and third, etc.) term(s) times the derivative of the second, etc.
If
  z = (f(x) g(x))
then the derivative of z is
  z ' = (f(x) g(x))'
    = f '(x) g(x) + f(x) g '(x)

So our example,

y = ( x - 1) ( x - 2) ( x - 3)
we can think of as
y = f(x) g(x) h(x)              
So the derivative is
y ' = ( f(x) g(x) h(x) )'              
  = f '(x) g(x) h(x) + f(x) g '(x) h(x) + f(x) g(x) h '(x)
  = ( x - 1 )' ( x - 2 ) ( x - 3 ) + ( x - 1 ) ( x - 2 )' ( x - 3 ) + ( x - 1 ) ( x - 2 ) ( x - 3 )'
and we just need to know each of the derivatives on the right-hand side of the equation. In this case these are
( x - 1 )' = 1 - 0 (by the derivative rule for sums, derivative rule for variables, and the derivative rule for constants)
( x - 2 )' = 1 - 0 (by the derivative rule for sums, derivative rule for variables, and the derivative rule for constants)
( x - 3 )' = 1 - 0 (by the derivative rule for sums, derivative rule for variables, and the derivative rule for constants)
so the finished derivative is
y ' = ( 1 - 0 ) ( x - 2 ) ( x - 3 ) + ( x - 1 ) ( 1 - 0 ) ( x - 3 ) + ( x - 1 ) ( x - 2 ) ( 1 - 0 )
  = (x - 2) (x - 3) + (x - 1) (x - 3) + (x - 1) (x - 2)
[]


additional explanation for the product rule
see another product rule example
practice gateway test
previous page
Page Generated: Thu Feb 6 20:39:34 2025
Comments to Gavin LaRose
glarose@umich.edu
©2001 Gavin LaRose, University of Michigan Math Dept.